Factors influencing health-promoting lifestyle among medical personnel: a systematic review protocol - Qi Zhang; Peng Huang; Dayang Shobihah Binti Abang Abai; Huajing Xiao; Zongji Xian; Karmilah Binti Abdullah (BMJ Open)
Introduction A health-promoting lifestyle is essential for improving quality of life and reducing the risk of chronic diseases. However, despite their high health literacy, medical personnel often show low adherence to such lifestyles. Identifying the factors influencing these behaviours in medical professionals is critical for developing effective interventions. This review aims to identify the factors that influence the health-promoting lifestyle among medical personnel.Methods and analysis We will conduct a systematic search across three electronic databases: Web of Science, Scopus and PubMed. To ensure comprehensive literature coverage, we will also examine the reference lists of included studies and relevant reviews identified during the search. Eligible studies will include quantitative, qualitative and mixed-methods research articles that investigate factors influencing health-promoting lifestyles among medical personnel. No restrictions will be applied regarding geographical location or publication year. Only original, peer-reviewed journal articles published in English will be considered. The search strategy will incorporate key terms and their synonyms, including Medical Subject Headings terms such as ‘factor’, ‘barrier’, ‘enabler’, ‘health-promoting lifestyle’, ‘medical personnel’, ‘doctor’, ‘nurse’, ‘medical technician’, ‘pharmacist’ and ‘hospital administrative staff.’ All retrieved studies will be imported into Rayyan software for duplicate removal. Two independent reviewers will conduct the screening process based on predefined inclusion and exclusion criteria. The risk of bias in individual studies will be assessed using the Mixed Methods Appraisal Tool. A narrative synthesis approach will be employed to synthesise findings, categorising identified influencing factors into five levels of the Ecological Model of Health Behavior: intrapersonal, interpersonal, organisational, community and public policy levels.Ethics and dissemination Ethical approval is not required as no original data collection is involved. Findings will be disseminated via peer-reviewed journals, conferences and the primary author’s PhD thesis.PROSPERO registration number CRD42024579746.